2003
DOI: 10.1007/s00438-003-0890-7
|View full text |Cite
|
Sign up to set email alerts
|

Real time RT-PCR quantification and Northern analysis of cerato-ulmin ( CU) gene transcription in different strains of the phytopathogens Ophiostoma ulmi and O. novo-ulmi

Abstract: Cerato-ulmin is a surface protein that belongs to the class of fungal proteins known as hydrophobins. This class II hydrophobin is produced throughout the life cycle and in all developmental stages of Ophiostoma novo-ulmi and O. ulmi; the aggressive and non-aggressive pathogens responsible for Dutch elm disease. Since yeast/mycelial transitions are often important to pathogenesis in dimorphic fungi such as Ophiostoma, we have examined the levels and abundance of cu mRNA in the yeast and mycelial stages of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Its role as a pathogenicity factor remains controversial, but it has been suggested that like Mad1 in M. robertsii , CU promotes the adherence of infectious spores to the cuticle of elm bark beetles [79]. The CU expression level was previously reported to be 20–60% higher in mycelium than in yeast cells that were grown in vitro [81]. Yet the CU gene was equally expressed in RNAseq data of yeast and mycelial forms [48].…”
Section: Discussionmentioning
confidence: 99%
“…Its role as a pathogenicity factor remains controversial, but it has been suggested that like Mad1 in M. robertsii , CU promotes the adherence of infectious spores to the cuticle of elm bark beetles [79]. The CU expression level was previously reported to be 20–60% higher in mycelium than in yeast cells that were grown in vitro [81]. Yet the CU gene was equally expressed in RNAseq data of yeast and mycelial forms [48].…”
Section: Discussionmentioning
confidence: 99%
“…The cu expression levels detected in Geosmithia were much lower than those reported for O. novo-ulmi (Tadesse et al 2003), thus raising the question of the functional significance of cu mRNA in the former species. The genomic fragment transferred between O. novo-ulmi and Geosmithia comprised 317 bp upstream to the coding sequence (Bettini et al 2010), a region where several putative regulatory motifs are present (Carresi et al 2008).…”
Section: Expression Of the Cu Gene In Geosmithia Speciesmentioning
confidence: 63%
“…The quantitative data from Real-Time PCR demonstrated that mycelium had twice the abundance of cu mRNA as compared to yeast and that the non-aggressive O. ulmi strain H5 produced 10 times less cu mRNA than the aggressive O. novo-ulmi strains H327 and VA-3O. The nonaggressive over-expressing mutant H5-tf16 had a cu mRNA abundance level that was 20 fold greater than the wild type O. ulmi H5 strain (Tadesse et al, 2003).…”
Section: Study Of Differential Gene Expression By Real-time Pcrmentioning
confidence: 98%
“…In parallel to constructing EST libraries for the discovery of novel genes in Ophiostoma, we began studying and quantifying the differential expression of known genes by Real-Time PCR (Tadesse et al, 2003). This relatively new technique combines reverse transcriptase-PCR with fluorescent probes in uniplex or multiplex reactions, to quantitatively measure gene expression in fungal cells recovered at different stages or in different environments.…”
Section: Study Of Differential Gene Expression By Real-time Pcrmentioning
confidence: 99%